ANALISIS YURIDIS AKIBAT HUKUM WANPRESTASI PADA PERJANJIAN PEMBIAYAAN DENGAN JAMINAN FIDUSIA (Studi Kasus Putusan Nomor: 13/Ptd.G.S/2021/PN.BDG) - Utami Yustihasana Untoro; Taufik Akbar Maulana; Tarmudi (Jurnal Hukum dan Bisnis (Selisik), 2022)
As the times progressed, so did human needs. So to fulfill this desire there is another way to do that is by borrowing debt. Over time, loan agreements do not always run smoothly. The existence of negligence or breach of contract (default) caused by one of the parties bound by the agreement creates legal consequences. Main issues (1) What are the judges considerations in dealing with default cases in financing agreements with fiduciary guarantees (case study of decision No. 13/Ptd.G.S/2021/PN.BDG) (2) What is the form of default in the financing agreement with fiduciary guarantee in decision no. 13/Ptd.G.S/2021/PN.BDG? The research method uses a case approach and normative juridical. Analysis, the form of default in consumer financing agreements with fiduciary guarantees in the decision Number: 13.Pdt.G./2021/PN.BDG, it was found that Mr. Muhamad Murmansyah as Defendant I and Ms. Delinda Zahra Zenita as Defendant II was legally proven to have committed a form of default. The Defendants committed acts of default in the financing agreement with fiduciary guarantees. The judge’s consideration in handling the default case in the financing agreement with fiduciary guarantees in the decision Number: 13.Pdt.G./2021/PN.BDG, has adhered to the principle of justice in adjudicating this case. The Panel of Judges has researched, examined carefully and investigated all actions, events, evidence and legal facts in the case files of this case. So it was found that the Defendants were indeed proven to be legally and actually violated Article 1238 of the Civil Code concerning Defaults in conjunction with Article 1243 of the Civil Code concerning compensation for losses and costs for the resulting legal consequences. The amount of compensation that must be paid by the Defendants is only Rp. 156,027,753 (one hundred fifty six million twenty seven thousand seven hundred and fifty three rupiahs)